Ecumenism in a Time of Transition. Issue 2 (7th November 2017) - Root, Michael
Abstract : To assess the present state and future possibilities of personal and ecclesial ecumenism between Protestant and Catholic Christians is a difficult task. On the one hand, the diversity among Protestants is so great few generalities hold for all of them. The challenges involved in Catholic relations with the Church of England are quite different than those involved in relations with the Southern Baptist Convention, and different in yet other ways from those involved in relations with a Pentecostal church in South Africa. In a broad sense, one can think of a spectrum of Protestant churches, some with whom Catholic relations might be close, and then a series of churches at a greater distance from Catholicism with whom relations would be more limited. That picture is only partially true, however. On many social issues, Catholics can work more closely with Evangelicals, with whom there are deep differences over sacraments and ecclesiology, than they can with more socially liberal representatives of, say, the Lutheran or Anglican traditions. In this brief reflection, I will be concerned with the Protestant communities with whom the greatest possibilities of a wide spectrum of closer relations seem to exist, such as the Anglican, Lutheran, and Reformed churches.